Achieving Racial Equity From the Bottom-Up? The Student Equity Policy in the California Community Colleges. Issue 6 (September 2020) - Ching, Cheryl D.; Felix, Eric R.; Fernandez Castro, Marlon; Trinidad, Adrián
Can equity policies foster success and close the outcome gaps experienced by racially minoritized students in community colleges? Using a critical policy analysis and equity-mindedness framework, we examine whether and how the design and early implementation of one such policy—the California Community Colleges' Student Equity Policy—addresses racial equity. Findings show that attention to race and racial equity diminished over time in state policy documents, and varied widely in colleges' response to the policy, suggesting that its potential to tackle racial inequities is so far unexploited. Implications are discussed and recommendations for policy, practice, and research are proposed.